2022
DOI: 10.1177/21582440221097920
|View full text |Cite
|
Sign up to set email alerts
|

Unhiding Nexus Between Service Quality, Customer Satisfaction, Complaints, and Loyalty in Online Shopping Environment in Pakistan

Abstract: Due to the recent development in online shopping, the e-commerce business has experienced significant growth. However, in developing nations such as Pakistan, the concept of e-commerce is yet in its early stages, and there are several roadblocks to users using this platform. Therefore, this study aimed to identify the nexus between service quality (SQ), customer satisfaction (CS), customer complaints, and loyalty in the online shopping environment by integrating the SQ model with the American Customer Service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 110 publications
0
25
0
3
Order By: Relevance
“…For example, by investigating online shoppers in developing nations, Wattoo et al found that service quality is positively associated with customer satisfaction, which leads to a reduction in customer complaints in an e-commerce context. 20 Depending on the results of in-depth interviews and questionnaire survey, Ravichandran and Deng found that frustration emotion is the best predictor for CCB toward the service provider. 65 The measure of this emotion is also reflected in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, by investigating online shoppers in developing nations, Wattoo et al found that service quality is positively associated with customer satisfaction, which leads to a reduction in customer complaints in an e-commerce context. 20 Depending on the results of in-depth interviews and questionnaire survey, Ravichandran and Deng found that frustration emotion is the best predictor for CCB toward the service provider. 65 The measure of this emotion is also reflected in this study.…”
Section: Discussionmentioning
confidence: 99%
“… 27 In the process of online shopping, the perception of products and services is the basic of the consumer’s shopping experience. 2 , 20 Thus, the specific discussion of these two perceived factors is carried out by the perceived product quality and perceived service quality, which are also the two exogenous variables and represent the “S” (stimulus) in this study of CCB.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“… Zeithaml et al (1996) revealed that brand loyalty represents the customers’ attempt to maintain a relationship with the target brand through a series of behaviors, mainly including the dissemination of word of mouth and repeat purchases, which will enhance the market competitiveness of the brand. Customer loyalty is the key to the formation of BM’s competitiveness and promotes online shopping of various products ( Wattoo and Iqbal, 2022 ). To establish a solid foundation of BM capacity, we must win considerable loyalty from the consumers.…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%